Application of the FISH technique to identify marker chromosomes detected in cell lines derived from laryngeal cancer - Szyfter, Krzysztof; Jarmuż, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2003)
A primary goal of cancer cytogenetics is to identify chromosomal aberrations typical for a given type of cancer or its stage. Only then is it possible to work on the clinical application of laboratory findings. Our own interest in cytogenetics of laryngeal squamous cell carcinoma was focused within this study on the structure identification of marker chromosomes already established in the cell lines derived from laryngeal cancer. The origin of marker chromosomes is by definition unknown. The fluorescence in situ hybridization (FISH) technique with the use of molecular painting probes was applied. The origin of five chromosomes previously described as marker chromosomes was explained as follows: the first marker chromosome was identified as isochromosome composed of short arms of chromosome 5 [i(5p]. The next three marker chromosomes resulted from unbalanced translocations between chromosomes 2 and 17[der(2)t(2,17) ], chromosomes 12 and 21[der(12)t(12,21,?)] and chromosomes 5 and 11 with additional duplication of a fragment of a long arm of chromosome 11[der(11)t (5,11)q(q14, q24)dup(11)(q23q24)]. Finally, a balanced translocation between chromosomes 13 and 15 was found to be the cause for the formation of the fifth marker chromosome [t(13,15)(p21.q12)]. A balanced translocation is a rare case in solid tumors. The identified marker chromosomes were mostly already described in head and neck tumors and i (5p) is relatively frequent. The found chromosome alterations provide a further proof for instability of genetic material in laryngeal cancer, reaching its peak in the centromere region.